2015
DOI: 10.1080/09524622.2015.1060531
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of ambient noise and habitat openness on signal transfer for chickadee vocalizations in rural and urban green-spaces

Abstract: Urbanization creates communication challenges for many species. Birds in particular rely on vocal communication for reproduction and territory defence, but in noisy or acoustically altered environments signals may be compromised. Both ambient noise and habitat openness affect signal transfer, but it is not clear how these two variables interact in urban green-spaces. Using black-capped and mountain chickadee vocalizations, we conducted transmission experiments to measure acoustic degradation and signal-to-nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Pitch shifting probably evolved as a mechanism to allow males to dynamically pitch-match (or avoid being pitchmatched by) rivals [28], but it may pre-adapt them with an efficient coping strategy to avoid signal masking from noise. Transmission experiments show that urban noise overlaps black-capped chickadee songs and has the potential to significantly reduce signal-to-noise ratios [29]. Further, observational and experimental exposure studies show that black-capped chickadees exhibit spectral plasticity in response to anthropogenic noise [30,31] and spectrally shift their songs away from narrow bands of overlapping noise [32].…”
Section: Introductionmentioning
confidence: 99%
“…Pitch shifting probably evolved as a mechanism to allow males to dynamically pitch-match (or avoid being pitchmatched by) rivals [28], but it may pre-adapt them with an efficient coping strategy to avoid signal masking from noise. Transmission experiments show that urban noise overlaps black-capped chickadee songs and has the potential to significantly reduce signal-to-noise ratios [29]. Further, observational and experimental exposure studies show that black-capped chickadees exhibit spectral plasticity in response to anthropogenic noise [30,31] and spectrally shift their songs away from narrow bands of overlapping noise [32].…”
Section: Introductionmentioning
confidence: 99%
“…The general noise levels experienced by focal males at each site (local ambient noise) ranged from 56 to 71 (median 65) dB(Z) for sites where we played High/Low playback pairs and from 53 to 71 (median 64) dB(Z) where we played Low/High playback pairs. Previous studies have shown that urban habitat structure has little effect on transmission of chickadee song relative to signal interference by urban noise conditions ( LaZerte, Otter & Slabbekoorn, 2015 ) and that it does not influence spectral adjustment in black-capped chickadees ( LaZerte, Slabbekoorn & Otter, 2016 ). Thus, although we conducted our study across a variety of habitat types to ensure an even sampling, we did not evaluate effects of habitat urbanization.…”
Section: Methodsmentioning
confidence: 99%
“…Pitch-shifting is thus a tool black-capped chickadees can, and do, use to spectrally adjust their vocalizations to higher frequencies in noisy conditions ( Proppe et al, 2012 ; LaZerte, Slabbekoorn & Otter, 2016 ) or to shift away, up or down, from narrow bands of masking noise ( Goodwin & Podos, 2013 ). Shifting to higher frequencies in noisy conditions is presumably adaptive as transmission studies show that black-capped chickadee songs are masked by anthropogenic noise ( LaZerte, Otter & Slabbekoorn, 2015 ). Furthermore, black-capped chickadees do not appear to have an innate tendency to respond more or less to low- versus high-frequency songs; Frequency-matching, instead of absolute frequency, is the important signal in male-male interactions ( Mennill & Otter, 2007 ), while females do not appear to differentiate at all ( Ratcliffe & Otter, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mountain chickadees (P. gambeli) sing whistled multi-note songs which vary considerably among populations (Grava, Otter, et al, 2013a;LaZerte, Otter, et al, 2017a), although in most populations consist of one or more high notes followed by several notes at a lower pitch. The song, particularly the lower-pitched elements, can be severely masked by urban noise (LaZerte, Otter, & Slabbekoorn, 2015). In noisy environments (typically urban landscapes), the lowest pitched notes are often higher in frequency than those in quiet areas (LaZerte, Otter, et al, 2017a).…”
Section: Ríosmentioning
confidence: 99%